Pemetaan Ilmiah Penelitian Manajemen Rantai Pasok untuk Usaha Mikro Kecil Menengah di ASEAN: Analisis Bibliometrik - Marina, Marina (Lembaga Pengembangan Manajemen dan Publikasi Imperium, 2025)
This study maps the scientific landscape of Supply Chain Management (SCM) for Small and Medium Enterprises (SMEs) in the ASEAN region through bibliometric analysis and network visualization. Using data from Scopus from 2009 to 2025, we identified 41 relevant papers from 36 different sources, showing an annual growth rate of 14.72% and international collaboration reaching 29.27%. The network visualization analysis revealed four main topic clusters: (1) a focus on SME/MSME digitalization, information technology, and business performance; (2) specific operational, decision, and manufacturing issues; (3) attention to sustainability and system dynamics; and (4) SCM core and economic aspects as a bridge. The most highly cited articles emphasized the crucial role of digitalization and big data analytics capabilities in improving SME SCM performance, particularly in Indonesia. A thematic shift from traditional operational aspects towards topics such as SME digitalization, sustainability, and resilience, with increasing contributions from ASEAN countries such as Indonesia, was also identified. The results of this study provide a comprehensive roadmap for academics, practitioners, and policymakers to understand the dynamics of SME SCM in ASEAN, identify trends, and direct future development efforts.